IMPLEMENTASI FUZZY LOGIC SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SEPEDA BERBASIS WEB - saputra, darian; Annurrallah Fajrin, Alfannisa (Computer Science and Industrial Engineering, 2022)
Toy'S Garden is one of the bicycle distributors in batam city, in carrying out some of its activities, toy's garden still uses the manual method in determining the bicycles to be sold, this cause can losses to its business, from this problem an application system is needed that can help in facilitating the selection bicycles to be marketed. This study discusses the decision making of bicycle selection with fuzzy logic mamdani method, with the design of a system, is expected to help facilitate activities in determining the type of bicycle to be sold. The results of manual defuzzyfication bicycles of BMX Garuda 20 got a value of 0.4 and the results of the MatLab test got a value of 0.24. The results of manual defuzzyfication bicycle of the MTB Podang 20 obtained a value of 0.33 and the results of the MatLab test got a value of 0.23. The result of manual defuzzyfication of the MTB Impressa Race 26 got a value of 0.25 and the result of the MatLab test got a value of 0.76. The result of manual defuzzyfication bicycle of the SA Princess 16 got a value of 0.33 and the result of the MatLab test got a value of 0.23. From the results of the manual accumulation and the MatLab application, bicycle of MTB Impressa race 26 will be chosen.